Teaching and Learning Languages in Multimedia Environments in Higher Education - Ruhil Amal, Azmuddin; Noor Raha, Mohd Radzuan (Universiti Malaysia Pahang, 2020)
With the current technological innovations in language teaching and learning fields, many higher education institutions (HEIs), particularly HEIs in Malaysia have integrated technological tools in and outside of classrooms. To support this move, education policies are being introduced to prepare ESL learners and instructors, particularly language instructors for the challenges in this technology-enhanced language learning milieu. This editorial section highlights pedagogical benefits for ESL learners from various e-learning environments which are adapted in higher education context, focusing on HEIs in Malaysia. The e-learning environments discussed include Computer-Assisted Language Learning (CALL), Learning Management Systems (LMS) and Computer-supported Collaborative Learning (CSCL). Blended learning and its benefits are also briefly addressed considering it to be an essential feature to successfully achieve a globalized online learning environment. With the integration of these technological tools in language classrooms, it is anticipated for learners to possess the necessary skills and competencies to be active participants in global communities in the future.